The effect of applying central line insertion and maintenance bundles in a renal dialysis unit – an effort to reduce CRBSI rate - Fouad, Mohammed Ahmed; Gabbad, Abdelsafi Abbas; AbdelRazik, Mahmoud (International Journal of Infection Control, 2015)
CRBSI rates were determined before and after the application of central line (CL) insertion and maintenance bundles by means of a prospective surveillance study conducted on patients undergoing regular catheter haemodialysis in the Artificial Kidney Unit of Al-Leith General Hospital, over a period of 12 months. During Phase 1 (baseline period), active surveillance was performed without the implementation of the infection control bundles. CRBSI rates obtained in Phase 1 were compared with CRBSI rates obtained in Phase 2 (intervention period), after implementation of the CL insertion and maintenance bundles. 2854 CL days were recorded during baseline period, 2,611 CL days were recorded during the intervention period. The CRBSI rate was 4.9 per 1,000 CL days in baseline period, and in the intervention period, the CRBSI rate decreased to 2.3 per 1,000 CL days. (Relative risk [RR] 0.48, 95% confidence interval [CI] 0.29–0.94, P = 0.02), showing a reduction of 52% in the CRBSI rate. This study shows that the implementation of CVC insertion and maintenance bundles was associated with a significant reduction in the CRBSI rates in the renal dialysis unit of a small hospital. Based on our study, we recommend that these bundles are protocol be adopted in all renal dialysis units.